Effective Comparison of Medicinal Plant Extraction to Anti Fungi on Vegetables - Sitthivohane, Insavai; Phouthaxay, Phonesavanh; Phomlasaboud , Khantavanh; VUE, Yong (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research was effective comparison of medicinal plant extraction to anti fungi on vegetables with the purpose of finding out the inhibit efficiency of fungi growth which was a cause of plant disease and different concentration of extraction. This analysis was established in laboratory of Faculty of Agriculture and Forest Resource, Souphanouvong University. It spent almost one month as 1st March – 25th March 2020. The experimental design was used Complete Randomized Design (CRD) consist of 3 Replication (R) and 5 Treatment (T). The result of research found that the inhibitive radius of pathogens as source of plant disease in each of medicinal plants in the laboratory was showed that when it was compared with positive control as direct antibiotics all species of medicinal plants has effective on fungi inhibition that was the source of plant disease in vegetable and it has potential statistically significant at p<0.05. In this experiment (Treatment) T1 has represented the highest of fungi inhibit efficiency which has large inhibitive radius of 7.66 mm, when compared with positive control it showed the rate of inhibition at 63.89%, in ordered number was T2, T4, T5 which has inhibitive radius of T2 = 7.00 mm, T4 = 7.00 mm, T5 = 6.66 mm, T3 has lowest inhibitive radius and either inhibit efficiency. However, all the treatments in each species were had well inhibit efficiency which it indicated the high inhibitive percentage when it has compared positive control as direct antibiotics. Moreover, the comparison between treatments showed that it had statistically significant at 95%. This analysis was recognized that the extracts from garlic leaves had fungi inhibition better than other medicinal plant species.